STRATEGI RSUD ARIFIN ACHMAD PROVINSI RIAU DALAM MELAKSANAKAN PROGRAM PENYEHATAN LINGKUNGAN GUNA MENINGKATKAN KEBERSIHAN DAN KEINDAHAN LINGKUNGAN RUMAH SAKIT - Junita M Saragih; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Arifin Achmad District Hospital is the largest hospital in the Province of Riau with type B education which every day provides a very intensive health services to the people, as the the biggest waste producers than the other health services. To prevent an infection is needed environmental sanitation which aims to improve the cleanliness and neatness of the hospital environment. Strategy of Arifin Achmad District Hopspital is the the steps that have been planned and implemented to improve the cleanliness and neatness of the hospital environment.This study aims to determine how the strategy of Arifin Achmad District Hospital and the factors that influence that strategy. This study uses qualitative research methods the study descriptive data. In data collection, researchers use interviewing techniques, observation and documentation specified by purposive sampling technique.The research result is a strategy of Arifin Achmad district hospital in implementing environmental sanitation program in order to improve the cleanliness and neatness of this case has not been effective due to it can not be able to optimize the power and opportunities. There are several factors that affect; lack of control, poor coordination, lack of hygiene and surveillance personnel as well as the low awareness of visitors and occupants of the hospital.Keywords : Cleanliness, Neatness, Enviromental Sanitation, Hospital, Strategy